PEMBERLAKUAN ASAS RETROAKTIF DALAM HUKUM PIDANA INDONESIA - Pande I Putu Cahya Widyantara; Anak Agung Sri Indrawati (Kertha Negara : Journal Ilmu Hukum, 2014)
Assessing criminal law, can not be separated with violations of the law,either offense or crime. In enacting the law shall respect the principle of legality,but also some criminal acts may impose Retroactive Principles. Therefore, it canbe observed regarding Retroactive application of the principles of substantivecriminal law and formal. For that, there needs to be a method that supports thetype of research that uses normative research (conflict norm). With the aim todetermine Retroactive application of the principle of substantive and formalcriminal law. Enforcement of criminal law retroactively, has been included in theLaw on human rights and terrorism for the Bali bomb case, a retroactiveapplication of the substantive criminal law. Retroactive Enforcement of principleby no means impossible that applies to the formal criminal law. Law Commissionas an example of the law governing the event that new evidence by electronicmeans applicable to a particular event. Retroactive enforcement of the principle ofthe Indonesian criminal law can only be applied to the criminal law and theprinciple Retroactive material and can not be applied to the formal criminal law ingeneral, but can be applied specifically to the formal criminal.